2012
DOI: 10.1007/s00428-012-1349-1
|View full text |Cite
|
Sign up to set email alerts
|

The development of chagasic megacolon requires severe denervation and the reduction in interstitial cells of Cajal number might be a contributing factor

Abstract: Bassotti and Villanacci [1], we would like to emphasize that in our study [2] we identified a reduced number of interstitial cells of Cajal (ICC) in chagasic megacolon (CM), as had been previously reported in studies by Hagger et al. [3] and Geraldino et al. [4]. Hypotheses were raised trying to explain the discrepancy with the results published by Iantorno et al. [5]. Bassotti and Villanacci [1] claim that the hypotheses we proposed (inclusion of mast cells and heterogeneous distribution of ICC in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
3
1
Order By: Relevance
“…We also noticed that well-preserved integral ganglia occur side by side with lesioned ones. Our findings challenge previous proposals that ganglionic neuronal depopulation is per se the cause of dysmotility and megacolon (González Cappa et al, 1987;Adad et al, 2001Adad et al, , 2013Jabari et al, 2012). We found that these alterations take place early in the acute phase, even though the symptoms and pathological findings manifest decades later, probably resulting from cumulative damage to neurons and other elements of the intestinal wall as well as progressive functional impairment, thus explaining some contradictory findings (Ribeiro et al, 1998;Meneghelli, 1999Meneghelli, , 2004Adad et al, 2001;Da Silveira et al, 2008;Jabari et al, 2012Jabari et al, , 2013.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…We also noticed that well-preserved integral ganglia occur side by side with lesioned ones. Our findings challenge previous proposals that ganglionic neuronal depopulation is per se the cause of dysmotility and megacolon (González Cappa et al, 1987;Adad et al, 2001Adad et al, , 2013Jabari et al, 2012). We found that these alterations take place early in the acute phase, even though the symptoms and pathological findings manifest decades later, probably resulting from cumulative damage to neurons and other elements of the intestinal wall as well as progressive functional impairment, thus explaining some contradictory findings (Ribeiro et al, 1998;Meneghelli, 1999Meneghelli, , 2004Adad et al, 2001;Da Silveira et al, 2008;Jabari et al, 2012Jabari et al, , 2013.…”
Section: Discussioncontrasting
confidence: 61%
“…One of the most challenging questions of CD is how T. cruzi leads to the manifestation of chronic intestinal lesions decades after infection and thus, when parasites are rare (Zhang and Tarleton, 1999 ; Tarleton, 2001 ; Benvenuti et al, 2008 ). The damage of myenteric neurons characterizes the chronic phase of the intestinal CD (Adad et al, 2013 ; Jabari et al, 2014 ). However, as the parasitism is very low in the lesions of digestive Chagas disease (da Silveira et al, 2005 ; Wesley et al, 2019 ), it has been suggested that chronic neuronal destruction might be due to the immune response that follows the infection, as proposed for heart lesions (Teixeira et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations